Small Forgotten Places in the Hearth of Cities On the residuality of public spaces in historical contexts: Florence as a case study - Laurìa, Antonio (People_Places_Architecture, 2021)
This book is the result of a research project designed and carried out at the Department of Architecture, University of Florence. This book discusses urban public spaces and, more specifically, run-down, inactive micro-spaces that are barely used due to their location, dimensions, morphology or semantic characteristics. In literature, these spaces are often defined as "residual urban spaces." A large abandoned industrial area on the outskirts of a town or a small interstitial space in a historical centre can be residual. With respect to such a broad subject matter, the book seeks to radically limit the field, concentrating on public residual spaces found in the oldest parts of cities. The book reflects on this theme and introduces a method for reading and assessment of the residuality of public spaces in historical contexts (Residuality Assessment Process) which was tested in the historical centre of Florence. It is the authors' view that residual spaces, above all if designed according to a system logic, can go from being problems to potential activators of urban and social regeneration processes, offering a useful contribution to improve city life.